Ciência, tecnologia e produção no Butantan - Chaimovich, Hernán (Revista USP, 2011)
The Butantan Institute (IB) is a São Paulo state public institution over a hundred years old. The scientific works produced by researchers at IB, as well as the international visibility of their results, have grown considerably in the last decade. The vaccines and hyperimmune serums produced at IB by means of its own techno-logy, which make up most of the products of this kind used in Brazil, have been object of scientific publications by IB researchers. The system which encompasses the Butantan Institute and the Butantan Foundation make up a one-of-a-kind institution in which basic research, technological development and production are gathered in one single space. That provides Brazil with immunobiologicals at the frontier where state-of-the-art knowledge and technology meet.